Influence of multiple gaseous medium injection on low-carbon iron ore sintering performance: Characteristics of natural gas and steam coupling injection. (10th November 2022) - Wu, Yufeng; Fan, Xiaohui; Ji, Zhiyun; Gan, Min; Tu, Yong; Zhao, Gaige; Zhou, Haoyu; Sun, Zengqing; Chen, Xuling; Huang, Xiaoxian; Zou, Fanqiu
Abstract: Hydrogen-rich gas and steam are widely regarded to be of great potential to mitigate CO2 emissions in iron ore sintering, these gases can regulate heat distribution in the sintering machines by replacing fossil fuels. However, most sintering machines only use one of the gases as the injecting medium, the potential of this technology has not been developed. In this paper, a multiple gaseous medium injection method contained natural gas and steam was experimentally investigated to solving this problem. Sintering tests were arranged to study the appropriate scheme of coupling injection and its influence on the sintering process, and the flue gas analyzer was used to detect the composition of the sintering flue gas in real time. Better sintering indexes were achieved by injecting the above two gaseous medium when the coke breeze ratio is unchanged, the results show that when 0.8 vol% natural gas is injected into the 4–14min, 0.15 vol% steam is injected into the 10–14 min, and 0.25 vol% steam is injected into the 15–18 min of sintering, the sintering yield increases by 2.42%, and the tumbler index increases by 2.72%. Under the above parameters, the coke breeze ratio can be reduced by 12.99%, the average NOx emissions decreased by 19.5%, and the average CO emissions decreased by 36.96% in the coupling injection interval (4–18min). After calculating the amount of coke breeze and natural gas in the optimal coupling injection sintering, CO2 emissions decreased by 7.66%, about 17.15 kg/t-sinter . Moreover, the PFR model was used to simulate the associated gas phase reaction after coupling injection which shows H2 O significantly reduced CO emissions and change the reduction pathway of NO. Generally, sintering fuel consumption and greenhouse gas emissions have also been reduced, providing theoretical support for the change of iron ore sintering energy structure. Graphical abstract: Image 1 Highlights: Natural gas and steam coupling injection in iron ore sintering for the first time. The energy structure is optimized to partial replace fossil fuel with gas-based fuel. The heat distribution and sintering speed after coupling injecting are analyzed. PFR model shows the NO reduction pathway will change when steam is present. CO2 emission can be reduced by 91400 t/year with coupling injection sintering.